2013
DOI: 10.1007/s10856-013-4883-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of third-body particles on wear rate in unicondylar knee arthroplasty: a wear simulator study with bone and cement debris

Abstract: The reduced intraoperative visibility of minimally invasive implanted unicondylar knee arthroplasty makes it difficult to remove bone and cement debris, which have been reported on the surface of damaged and retrieved bearings. Therefore, the aim of this study was to analyze the influence of bone and cement particles on the wear rate of unicompartmental knee prostheses in vitro. Fixed bearing unicompartmental knee prostheses were tested using a knee-wear-simulator according to the ISO standard 14243-1:2002(E) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…Retrieval studies have shown a relation between third-body particles, increased roughness of the femoral condyles, and increased polyethylene wear [ 32 , 33 ]. This has also been confirmed by in vitro wear studies that determined increased polyethylene wear in the presence of cement particles in knee joint replacements [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Retrieval studies have shown a relation between third-body particles, increased roughness of the femoral condyles, and increased polyethylene wear [ 32 , 33 ]. This has also been confirmed by in vitro wear studies that determined increased polyethylene wear in the presence of cement particles in knee joint replacements [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, it is expected that cement particles may also contribute to the wear performance of the final joint replacement. As third-body wear particles, they are able to accelerate wear processes, particularly when radio-opaque substances such as barium sulphate or zirconium dioxide are involved [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the knee wear simulator it is necessary to test both condyles, so we therefore chose the same implant on the lateral side to create a placeholder during testing. This technique has also been established by other groups [ 14 , 15 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 97%
“…The cohesion between the tissues and pure ceramics is also lower than the cohesion of autografts, which might cause particles to spread around the surgical field during implantation [35,36]. Grafting near the joints might cause loose particles to migrate between joint surfaces, and thus create third-body wear [37]. In our study, the new β-TCP/PLCL scaffold was easily moldable and adaptable to the anatomical convex contour of the skull, even though the ceramic concentration of the scaffold was 50 weight-%.…”
Section: Discussionmentioning
confidence: 99%